(untitled) (Agricultural Engineering, 2022)
The paper presents the results of the research on the influence of the adjuvant concentration on the size of the drops produced by the spray nozzles of agricultural sprayers. For the tests, adjuvant Normaton with the composition of total nitrogen, amide nitrogen (N-NH2) and phosphorus pentoxide (P2O5) was used. The adjuvant was added to the water taken from the municipal water supply system of the city of Lublin. The tests were carried out for three concentrations, i.e. 75%, 100%, and 125% of the adjuvant concentration recommended by the manufacturer, and water without the adjuvant. The surface tension of water with adjuvant was examined for each nozzle. Then, the size of the obtained droplets was measured for each adjuvant concentration. Two types of nozzles were used for spraying, standard nozzle AP 120-03 and 6MSC injector nozzle, both with the same nozzle flow rate, but with a different design. The size of the droplets produced was measured on a HELOSVARIO laser diffractometer by Sympatec. The droplet measurement was performed at a pressure of 3 bar. The nozzle was placed 50 cm above the diffractometer laser light line. The droplet size was measured in three places of the sprayed liquid, i.e. in the position of the nozzle axis, 30 and 60 cm from the nozzle axis. It was shown that the addition of the adjuvant influenced the number of droplets produced in the indicated droplet size classes.